Enhancing EFL Learners’ English Reading Performance through the Diagnostic Feedback of CDA - Sun, Huihui; Hwang, Yohan (Korea Journal of English Language and Linguistics, 2023)
Cognitive Diagnostic Assessment (CDA) enhances the value of assessments by accurately diagnosing learners’ strengths and weaknesses in specific fields. It provides an invaluable opportunity for individualized teaching and targeted remediation. The primary objective of this paper is to enhance the reading section of the College English Test Band Four (CET-4) in China by incorporating the G-DINA cognitive diagnostic model and proposing a comprehensive teaching framework to effectively address students’ weaknesses. To achieve this objective, diagnostic information is obtained using the G-DINA cognitive diagnostic model, specifically from the reading section of CET-4. In order to integrate the diagnostic information into the classroom setting, a novel strategy instruction framework is proposed. To assess its effectiveness, a comparative teaching experiment is conducted. The findings of the study highlight that the reading section of CET-4 serves as a powerful tool for identifying learners’ weaknesses in reading. Furthermore, the proposed framework demonstrates significant improvements in students’ reading performance. These compelling results indicate that CDA outperforms other traditional assessment methods, showcasing its superior instructive nature. Based on these insightful findings, this study suggests the adoption of CDA as a more comprehensive and impactful approach to assessment, as it not only diagnoses learners’ strengths and weaknesses but also provides valuable insights for personalized instruction and targeted remediation. KCI Citation Count: 0